Life of Tukaram - Mundadan, A M (Journal of Dharma, 1984)
Justin E. Abbot, trans. and ed. Life of Tukaram (translation from Mahipati's Bhaktalilamrita, chapters 25 to 40) Motilal Banarsidass, 1980. (Reprint of the first edition, Poona, 1980), pp. n +346, Rs. 45/-